The Impact of Artificial Intelligence on the future of jobs in the South African automotive sector - Setati, Portia (University of the Witwatersrand, Johannesburg, 2024)
This report attempted to provide insights on the impact of Artificial Intelligence on the future of work in the automotive industry. The aim of this paper was to identify the potential benefits and challenges of AI adoption in the automotive sector and to develop strategies to maximize the benefits while mitigating the risks. South Africa, a significant player in the global automotive market, faces unique challenges and opportunities as AI integration progresses.The study employed a qualitative method approach and conducted semi-structured interviews to gather data. By examining current trends and future projections, the research interprets how AI technologies are reshaping traditional automotive manufacturing processes and workforce dynamics.Findings suggest that while AI adoption promises enhanced productivity, efficiency, and product quality, it also poses challenges in terms of workforce displacement, skill gaps,and job redefinition. The South African automotive industry, characterized by a diverse workforce and socio-economic disparities, must navigate these changes with a strategic approach to ensure inclusive growth and equitable distribution of opportunities.This research contributes to a deeper understanding of the transformative impact of AI on the future of work in the South African automotive industry, offering insights into the opportunities and challenges that lie ahead and proposing strategies for harnessing AI's potential for inclusive and sustainable growth
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Robotics; Future of work; Artificial Intelligence; Automation; AI adoption; AI algorithms; UCTD; SDG-9: Industry, innovation and infrastructure